The Influence Of Scholastic Philosophy on the Formation of Economic Thought - de melo, gabriel estruzani queiróz (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The present study analysis the influence that scholastic philosophy had on the formation of fundamental concepts in economic thought. It shows scholastic considerations on market self-regulation, trade, fair price, value theory, competition, property, inflation and the value of money. The University of Salamanca deserves prominence both because it was the cradle of free market economic theories and because it tried to reconcile economic ideas with the moral and historical bases of Judeo-Christian matrix, which always guided the scholastic thinkers. Through bibliographical and historical research, both of primary sources and of later studies, the present work shows the scholastic roots of contemporary economic schools of thought and the relationship between the concepts they use and their original authors.